Reflections on the 1917 Russian Revolution in George Orwell's Animal Farm: M.H. Abrams' Mimetic Approach - Dyah Shofiah; Purwani, Wilujeng Asih (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study analyzes George Orwell's novel Animal Farm as a reflection of social conflicts in the 1917 Russian Revolution using M.H. Abrams' mimetic approach. The novel functions as an allegory, with Mr. Jones representing Tsar Nicholas II, Snowball as Leon Trotsky, and Napoleon as Joseph Stalin. Through the mimetic approach, this research identifies how the rebellion, power struggles, and the corruption of revolutionary ideals are depicted in the novel, ultimately leading to dictatorship that mirrors the regime they initially rejected. Orwell highlights how the revolution's original vision of equality was ultimately betrayed by the new leaders. The findings of this study show that Animal Farm not only critiques Stalinism but also reflects broader social and political phenomena related to the concentration of power, abuse of authority, and the cyclical nature of power in history. This study supports mimetic theory by demonstrating how literature can deeply reflect historical realities, contributing to the discourse in both literature and politics, and serving as a reminder of the dangers of authoritarianism.